El uso de los sujetos pronominales explícitos y nulos por los aprendices de ELE - Bran, Rǎzvan (Acta Hispanica, 2015)
This paper aims to analyse the errors made byRomanian students who learn Spanish as aForeign Language in using pronominal and nullsubjects. Neither Romanian (students´ L1) norSpanish require pro subjects, but after investigatingthe corpus (including opinion essays andnarratives), we have noticed that pronominalsubjects are misused. In our view, one possibleexplanation of this syntactic error could be theinterference with other foreign languages thatstudents learn, which are pro-drop languages.This type of error appears more often in thefirst stage of interlingua and the more advancedthe student is, the less errors he makes. As thesyntactic competence is fundamental in theacquisition process of the L2, it is veryimportant this phenomenon to be reckonedboth by students and by teachers.